CERTAIN CONSIDERATIONS ABOUT THE RIGHT TO WORK AND THE REINSTATEMENT OF AN EMPLOYEE AFTER UNLAWFUL DISMISSAL - Marta-Claudia CLIZA; Laura-Cristiana SPĂTARU-NEGURĂ (Challenges of the Knowledge Society)
The consequences of finding by a court of law that the decision to dismiss an employee is void, are to annul with retroactive effect the measure terminating the employment relationship between the parties (i.e. the applicant and the employer) and to restore the previous situation. According to the retroactivity principle of the effects of the legal act nullity - nullity does not produce effects only for the future (ex nunc), but also for the past (ex tunc), i.e. these effects are produced up to the moment of the conclusion of the civil legal act. The most important consequence of the annulment of the dismissal decision and the reinstatement of the previous situation is the effective reinstatement in employment. Reinstatement means the continuation of the old employment agreement (without changing its provisions - including the place of work or salary), by resuming the position previously held. In this study we shall tackle down certain considerations regarding the proper reinstatement of an employee, without breaching his or her legal rights, including the right to work.